Upaya Penegakan Nilai-Nilai Pancasila dalam Rangka Mengatasi Isu Kekerasan Seksual di Lingkungan Kampus di Riau - Neysa Audi M; Amelia Sekar Ayu Pramesti; Rifa Mitra; Zona Oktavia; Lathifa Munawarah; Dara Kesumadewi; Ilham Hudi (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
In Indonesia, sexual assault on campuses is against Pancasila ideals and has to be expected right away. Examining sexual assault on campuses from a Pancasila viewpoint is the goal of this study. A literature review is conducted as part of a qualitative procedure. The study's findings indicate that the number of incidences of sexual assault has been rising significantly over the last several years. The ideals of Pancasila, including social justice and a fair and civilised humanity, are in direct opposition to this sexual assault. Therefore, in order to prevent and end sexual assault on campuses, sexual education that incorporates Pancasila ideals must also be implemented there.